Juvenile and Mature Performances of Handpollinated Rubber Progenies and the Implication in Hevea Breeding - Le, Mau Tuy (1998)
The RRIM's 1988 Hand-Pollination Programme was conducted using two different sources of materials. e.i. Wickham and Amazon. The progenies obtained from the Hand-Pollination Programme were used to establish a Seedling Evaluation Trial at RRIM Experiment Station, Sungai Buloh. Test tapping was carried out at three and half years after planting. The trial was opened for normal tapping at seven years old. The p erformances of progenies using data both at immature and mature stages were studied. Generally. progenies from W x Am crosses were inferior to that of W x W crosses in latex yield. However. there was a W x Am family (PB 5/51 x 64/151) and produced high yield in normal tapping that was comparable to the best of W x W families. High correlation (r = 0. 972) was found between the two test tapping yield characters (mean yield over three cycles and five cycles of tapping). The correlation between normal tapping yield and the two test tapping yields were significant but lower (r = 0.660 and 0.715, respectively). The family ranking order based on yield of normal tapping in comparison with that on yield of test tapping was not very much different except for few cases. There were families that produced better yield at normal tapping than in test tapping and vice versa. Selection for top 10% yield of test tapping can get only about half of expected individuals in the same proportion selected on yield at normal tapping.